The multifunctional role of leukaemia inhibitory factor in cutaneous biology - Szepietowski, Jacek C. (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2004)
Leukaemia Inhibitory Factor (LIF) is a polyfunctional cytokine, that belongs to the family of haemopoietic growth factors. LIF plays a role in growth-promotion and differentiation, regulates calcium and bone metabolism, induces acute phase proteins and causes cachexia in organisms with neoplastic disorders. LIF is also to be found in normal skin, where it may be involved inthe differentiation process of keratinocytes. In addition, recent data in medical literature indicates that LIF is engaged in the pathogenesis of some skin disorders as well. It has been clearly demonstrated that LIF may act as aproinflammatory cytokine. In allergic contact dermatitis, the expression of LIF mRNA is augmented to a significant degree, indicating that LIF may play a role in the early phase of allergic contact dermatitis. LIF also plays an important role in psoriatic lesions. As the mechanism is not yet fully understood, however, it is hypothesized that the LIF function in psoriatic processes is solely connected with IL-8, as it is known that LIF is able to induce the release of IL-8. Also, some reports have suggested that LIF may play a role in the carcinogenesis of the skin.
Keywords: Dermatitis alergijski, kontaktni; Dermatitis, Allergic Contact; dermatologija; Hematopoetske celice, rastni faktorji; Hematopoietic Cell Growth Factors; Immunology; Keratinociti; Keratinocytes; ko.ne bolezni; Kožne novotvorbe; Psoriasis; Psoriaza; rak (medicina); Skin Neoplasms